Constructing the 32-item Fitness-to-Drive Screening Measure. (April 2018) - Medhizadah, Shabnam; Classen, Sherrilene; Johnson, Andrew M.
The Fitness-to-Drive Screening Measure © (FTDS) enables proxies to identify at-risk older drivers via 54 driving-related items, but may be too lengthy for widespread uptake. We reduced the number of items in the FTDS and validated the shorter measure, using 200 caregiver responses. Exploratory factor analysis and classical test theory techniques were used to determine the most interpretable factor model and the minimum number of items to be used for predicting fitness to drive. The extent to which the shorter FTDS predicted the results of the 54-item FTDS was evaluated through correlational analysis. A three-factor model best represented the empirical data. Classical test theory techniques lead to the development of the 32-item FTDS. The 32-item FTDS was highly correlated ( r = .99, p = .05) with the FTDS. The 32-item FTDS may provide raters with a faster and more efficient way to identify at-risk older drivers.